Sometimes brilliant : the impossible adventure of a spiritual seeker and visionary physician who helped conquer the worst disease in history - Brilliant, Lawrence B. (HarperOne, 2016)
"The unforgettable, entertaining, and inspiring memoir of the activist, teacher, entrepreneur, and spiritual leader that illuminates some of the most revolutionary events of a generation, many of the legendary people who defined it, and a towering figure at the center of it. Larry Brilliant's life journey has led him on a purposeful path across continents and countercultural movements, marching arm-in-arm with the men and women who defined a generation. A man who has always been in the right place at the right time, Brilliant has engaged with some of the most prominent thought leaders, spiritual masters, heroes, and icons in the world, including Neem Karoli Baba (Maharajji), Martin Luther King, Jr., Steve Jobs, Mikhail Gorbachev, Wavy Gravy, the Grateful Dead, the Dalai Lama, and Barack Obama. But this self-proclaimed "typical Jewish kid from Detroit" was no accidental witness to history. Brilliant is a force of nature in his own right, responsible for some of the most significant medical, spiritual, and social achievements of the past century--from the eradication of smallpox and treatment of blindness to introducing the teachings of the Maharajji to the Woodstock Generation, to launching Google's philanthropic enterprises. Now for the first time, Brilliant reflects on his remarkable life and his extraordinary experiences as a doctor, innovator, philanthropist, and cultural revolutionary. As he recalls the past fifty years and all that he has seen and done, this masterful storyteller offers transformative messages of wisdom and compassion that will inspire everyone to work towards a better, more brilliant existence. His is a truly cinematic and fun journey--and a profound search for meaning that provides a new perspective on what it means to be engaged with life's most important questions"--